SPOILAGE OF SPOTTED SEER(SCOMBEROMOROUS GUTTATUS) DURING ICE STORAGE. - SHENOY, A VASANTH (Fishery Technology, 2017)
Quality deterioration of seer h.eld directly in contact with ice, in different forms, fillets and chunks, and of chunks held in ice but without direct contact, was studied for a period of 15 days. While the chunks held out of contact with ice were acceptable upto 13 days based on organoleptic evaluations, the chunks and fillets held in direct contact with ice were acceptable only upto 10 days. The order of preference of the samples at any interval of ice storage was chunks held out of contact with ice> chunks held directly in ice> fillets held directly in ice. The changes in the chemical quality of these samples were also in the same order, the deterioration being maximum in fillets and least in chunks kept out of contact with ice.